2001
DOI: 10.1023/a:1013574413217
|View full text |Cite
|
Sign up to set email alerts
|

Do all patients with advanced non-small-cell lung cancer benefit from cisplatin-based combination therapy?

Abstract: PS 2 patients with advanced NSCLC might not benefit from cisplatin combination therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(21 citation statements)
references
References 17 publications
4
17
0
Order By: Relevance
“…The four independent poor factors that were identified in the initial characteristics of the present patients were male sex, anaemia, weight loss and poor Karnofsky PS. This is in accordance with the present authors' previous trials, and with the studies specifically performed on poor PS [18,19] but does not imply that patients do not benefit from chemotherapy. An overall survival improvement with chemotherapy versus supportive care alone in patients with poor PS has been shown by the Nonsmall Cell Lung Cancer Collaborative Group meta-analysis [20].…”
Section: Chemotherapy For Low Ps Nsclc Patients Jp Sculier Et Alsupporting
confidence: 93%
See 1 more Smart Citation
“…The four independent poor factors that were identified in the initial characteristics of the present patients were male sex, anaemia, weight loss and poor Karnofsky PS. This is in accordance with the present authors' previous trials, and with the studies specifically performed on poor PS [18,19] but does not imply that patients do not benefit from chemotherapy. An overall survival improvement with chemotherapy versus supportive care alone in patients with poor PS has been shown by the Nonsmall Cell Lung Cancer Collaborative Group meta-analysis [20].…”
Section: Chemotherapy For Low Ps Nsclc Patients Jp Sculier Et Alsupporting
confidence: 93%
“…Patients with poor PS represented 20% of the patients registered in the present trial, a prevalence similar to that reported in other studies [9,18,19,21]. Responses were not observed much less frequently in those patients than in those of good PS.…”
Section: Chemotherapy For Low Ps Nsclc Patients Jp Sculier Et Alsupporting
confidence: 89%
“…Indeed, such combinations may be an option for patients unable to tolerate platinum agents or those with compromised performance status. In addition, patients with a performance status of 2 do not benefit from platinum-based chemotherapy (Soria et al, 2001). In general, studies comparing non-platinum regimens with platinum-based regimens are still ongoing.…”
Section: Other Chemotherapy Optionsmentioning
confidence: 99%
“…Advanced NSCLC patients also with poor performance status (PS) tend to have worse response rates and higher risk of toxicities following chemotherapy treatment. 4,5 Intracellular signaling activated by the EGFR plays a role in tumor growth and progression in cancer and EGFR overexpression is seen in up to 80% of NSCLC6,7. Erlotinib is a potent, orally active, reversible inhibitor of EGFR tyrosine-kinase activity and have received approval for the treatment of advanced NSCLC worldwide.…”
Section: Introductionmentioning
confidence: 99%